Nutritional analysis of diet at base camp of a seven thousand-metre mountain in the Himalayas - M. Mariscal-Arcas (Revista Andaluza de Medicina del Deporte, 2010)
Objective. To evaluate the diet of a group of high-mountain climbers at 4,500 metres. Methods. A descriptive cross-sectional study was performed on the diet of a group of high-mountain climbers at their base camp (4,500 m). Results. The mean intake was 11.85 MJ/day (2,833 kcal/day), which provided an inadequate supply of energy and micronutrients to replenish deposits. Their mean carbohydrate intake (39.5%) was excessively low, since carbohydrate-rich diet favours acclimatization and the capacity for recovery. Their daily intake of 1.5-2.5 g/protein/kg of bodyweight was very similar to recommendations (1.5-2.0 g/kg/day). Conclusions. The climbers underwent a drastic change from their habitual Mediterranean diet, rich in monounsaturated fats (largely olive oil), to a diet rich in polyunsaturated fats (largely soy oil). The Sherpa- prepared diet on this expedition was not balanced. It was rich in saturated polyunsaturated fats and relatively poor in proteins and especially carbohydrates, similar to the traditional diet of climbers. Dietary strategies need to be developed to increase the intake of nutrients that favours the physical recovery of climbers and their altitude-acclimatization and to avoid micronutrient deficiencies.